Probing Strangeness Hadronization with Event-by-Event Production of Multistrange Hadrons - Acharya, S.; Adamovã, D.; Agarwal, A.; Aglieri Rinella, G.; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; et al. (American Physical Society, 2025)
This Letter presents the first measurement of event-by-event fluctuations of the net number (difference between the particle and antiparticle multiplicities) of multistrange hadrons Ξ − and Ξ ¯ + and its correlation with the net-kaon number using the data collected by the ALICE Collaboration in pp, p-Pb, and Pb-Pb collisions at a center-of-mass energy per nucleon pair s NN = 5.02 TeV . The statistical hadronization model with a correlation over three units of rapidity between hadrons having the same and opposite strangeness content successfully describes the results. On the other hand, string-fragmentation models that mainly correlate strange hadrons with opposite strange quark content over a small rapidity range fail to describe the data.
Keywords: Hadronization; Physics; Hadron; Particle physics; Rapidity; Nuclear physics; Strangeness; Strange quark; Strangeness production; Event (particle physics); Quark; https://purl.org/pe-repo/ocde/ford#1.03.03